2019
DOI: 10.1097/shk.0000000000001146
|View full text |Cite
|
Sign up to set email alerts
|

Amitriptyline Treatment Mitigates Sepsis-Induced Tumor Necrosis Factor Expression and Coagulopathy

Abstract: During sepsis, the early innate response and inflammatory cytokine cascade are associated with activation of the coagulation cascade. Acute hypercoagulability can contribute to lethal sequela of vascular thrombosis, tissue ischemia, and organ failure. We investigated if amitriptyline (AMIT), an antidepressant drug with a number of anti-inflammatory effects, could ameliorate sepsis in a murine model of sepsis - cecal ligation and puncture (CLP). We hypothesized that AMIT treatment would reduce inflammation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…All animal protocols were approved by the Institutional Animal Care and Use Committee at the University of Cincinnati (Protocol 10-05-10-01). To induce acute polymicrobial sepsis, mice underwent 33% cecal ligation with a single, full-thickness, 25-gauge needle puncture under 2.5% isoflurane general anesthesia, as previously described (26,32). All surgeries were performed between 8 AM and 12 PM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All animal protocols were approved by the Institutional Animal Care and Use Committee at the University of Cincinnati (Protocol 10-05-10-01). To induce acute polymicrobial sepsis, mice underwent 33% cecal ligation with a single, full-thickness, 25-gauge needle puncture under 2.5% isoflurane general anesthesia, as previously described (26,32). All surgeries were performed between 8 AM and 12 PM.…”
Section: Methodsmentioning
confidence: 99%
“…Murine data focused on coagulopathy and PICS are also limited. We recently reported that, after cecal ligation and puncture (CLP), mice were acutely hypercoagulable, but 16 h after injury, they became hypocoagulable (32). These data raise the question of whether coagulation abnormalities continue even after acute infection or sepsis subsides.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the understanding the dynamics of IL-10 expression is essential. Several studies showed time-dependent effects of IL-10 administration or inhibition in sepsis models (75)(76)(77). Given the fact that IL-10 expression is upregulated quickly after trauma and sepsis, as described in the previous section, it seems likely that in the beginning, lower levels of IL-10 may stimulate bacterial clearance but impair functions when the serum levels exceed a certain threshold.…”
Section: Effects and Drivers Of Pathological Release In Trauma And Sementioning
confidence: 96%
“…(C) The dynamics of the immune perturbation in trauma and sepsis was modeled in recent literature (74). In general a time dependent modulation of IL-10 levels might restore immune hemostasis (75)(76)(77). Animal models suggest a beneficial effect of early IL-10 application (76) and the correlation of elevated IL-10 levels and injury severity suggests beneficial effects by IL-10-blockage in later phases (31,45,78).…”
Section: Dynamics In Trauma and Sepsismentioning
confidence: 99%
See 1 more Smart Citation